Paradoxical kinesia in Parkinson's disease revisited: Anticipation of temporal constraints is critical - Distler, Michael; Schlachetzki, Johannes; Kohl, Zacharias; Winkler, Jürgen; Schenk, Thomas (Neuropsychologia, 2016)
Slowness of movement, called bradykinesia is the cardinal symptom of Parkinson's disease. Under distinct but not yet well-defined circumstances, patients with Parkinson's disease are able to overcome bradykinesia. One common hypothesis for this phenomenon termed paradoxical kinesia in Parkinson's disease postulates that the presentation of external sensory triggers is pivotal to elicit significant increase of motor velocity. In the present study, we examined an alternative hypothesis, namely that an internal cue in the absence of sensory cues are linked to paradoxical kinesia. To test this alternative hypothesis, patients with Parkinson's disease and healthy age-matched controls (n=9 per group) performed two movement tasks. In the stationary-object prehension task, subjects had to pick up a stationary target object. For the escaping-object task, the participants had to pick up the target object before it moved out of reach. The time available to reach for the object was adjusted individually to ensure comparable difficulty across participants. Reaction time, movement duration, and maximum velocity were assessed for both movement tasks. In Parkinson's disease patients and healthy controls, anticipation of the imminent movement of a target object significantly decreased reaction time, movement duration, and increased maximum movement velocity. The increase of maximum movement velocity in the escape-condition was significantly more pronounced for Parkinson's disease patients as compared to healthy controls. We provide evidence that internal cues such as temporal constraints are sufficient to diminish the cardinal clinical symptom of bradykinesia in Parkinson's disease. Our results suggest that expectations rather than sensory cues are critical for the emergence of paradoxical kinesia and we discuss the implications of our findings for an account of paradoxical kinesia.
EVALuna2:33521